Obscurité des Lumières : les prisons d’Europe, d’après John Howard, autour de 1780 - Petit, Jacques-Guy (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1995)
John Howard's State of Prisons portrays British prisons toward 1780 as places of injustice and arbitrariness, where conditions of detention were anything but humane. Continental prisons hardly appear better, except for some that Howard presents as models. After some years of easy life in the gentry, Howard devoted himself to his Grand Tour of European prisons. A philanthropist of his times, he analyzed prisons from a point of view that remains just as relevant today as it was 200 years ago.